The incidence of cervical spondylosis decreases with aging in the elderly, and increases with aging in the young and adult population: a hospital-based clinical analysis - Wang C (Dove Medical Press, 2016)
Chuanling Wang,1,* Fuming Tian,1,* Yingjun Zhou,2 Wenbo He,1 Zhiyou Cai1 1Department of Neurology, 2Physical Examination Center, Renmin Hospital, Hubei University of Medicine, Shiyan Renmin Hospital, Shiyan, Hubei Province, People’s Republic of China *These authors contributed equally to this work Background and purpose: Cervical spondylosis is well accepted as a common degenerative change in the cervical spine. Compelling evidence has shown that the incidence of cervical spondylosis increases with age. However, the relationship between age and the incidence of cervical spondylosis remains obscure. It is essential to note the relationship between age and the incidence of cervical spondylosis through more and more clinical data.Methods: In the case-controlled study reported here, retrospective clinical analysis of 1,276 cases of cervical spondylosis has been conducted. We analyzed the general clinical data, the relationship between age and the incidence of cervical spondylosis, and the relationship between age-related risk factors and the incidence of cervical spondylosis. A chi-square test was used to analyze the associations between different variables. Statistical significance was defined as a P-value of less than 0.05.Results: The imaging examination demonstrated the most prominent characteristic features of cervical spondylosis: bulge or herniation at C3-C4, C4-C5, and C5-C6. The incidence of cervical spondylosis increased with aging before age 50 years and decreased with aging after age 50 years, especially in the elderly after 60 years old. The occurrence rate of bulge or herniation at C3-C4, C4-C5, C5-C6, and C6-C7 increased with aging before age 50 years and decreased with aging after age 50 years, especially after 60 years. Moreover, the incidence of hyperosteogeny and spinal stenosis increased with aging before age 60 years and decreased with aging after age 60 years, although there was no obvious change in calcification. The age-related risk factors, such as hypertension, hyperlipidemia, diabetes, cerebral infarct, cardiovascular diseases, smoking, and drinking, have no relationship with the incidence of cervical spondylosis.Conclusion: A decreasing proportion of cervical spondylosis with aging occurs in the elderly, while the proportion of cervical spondylosis increases with aging in the young and the adults. This investigation implicates that aging is not only a contributor to the clinical performance of cervical spondylosis in the elderly, although the incidence of cervical spondylosis is proportional to the progress of age. Keywords: cervical spondylosis, incidence, aging, risk factor